Epigenetic silencing of Kruppel like factor-3 increases expression of pro-metastatic miR-182. Issue 1 (1st December 2015) - Sachdeva, Mohit; Dodd, Rebecca D.; Huang, Zhiqing; Grenier, Carole; Ma, Yan; Lev, Dina C.; Cardona, Diana M.; Murphy, Susan K.; Kirsch, David G.
Highlights Klf-3 is a novel transcriptional repressor of pro-metastatic miR-182 in sarcomas. Klf-3 suppresses a myogenic transcription factor MyoD1. Klf-3 is epigenetically silenced by DNA hypermethylation. Demethylating agents could potentially be used to modulate miR-182 levels as a therapeutic strategy.